DRIVING SUSTAINABLE CONSUMPTION: THE ROLE OF GREEN PRODUCT AND GREEN PROMOTION IN SHAPING ENVIRONMENTAL AWARENESS AND PURCHASE DECISIONS - Koesworodjati, Yudhi; Aulia, Yasmin (Faculty of Economic and Business, University of Pasundan, 2025)
Plastic waste constitutes the second-largest type of waste in Bandung City, with mineral water bottles as the main contributor. Danone-AQUA, as the leading bottled water brand in Indonesia, significantly contributes to this issue. This study investigates the influence of green products, green promotion, and environmental awareness on green product purchase decisions among AQUA consumers in Bandung. A descriptive and verification research design was employed with a sample of 100 respondents selected through observation, interviews, and questionnaires. Data were analyzed using path analysis, the coefficient of determination, and hypothesis testing. The findings reveal that green products and green promotion simultaneously affect environmental awareness by 49.1%, with partial contributions of 27.7% and 21.4%, respectively. Furthermore, green products, green promotion, and environmental awareness jointly influence purchase decisions by 60.6%. Partially, green products contribute 17.7%, green promotion 23.5%, and environmental awareness 19.4%. These results highlight the critical role of environmental awareness in shaping consumer behavior toward sustainable purchasing.